Deep blue fluorophores incorporating sulfone-locked triphenylamine: the key for highly efficient fluorescence–phosphorescence hybrid white OLEDs with simplified structure. Issue 27 (15th June 2015) - Li, Yunchuan; Li, Xiang-Long; Cai, Xinyi; Chen, Dongcheng; Liu, Xin; Xie, Gaozhan; Wang, Zhiheng; Wu, Yuan-Chun; Lo, Chang-Cheng; Lien, A.; Peng, Junbiao; Cao, Yong; et al.
Abstract : Deep blue fluorophors incorporating sulfone-locked triphenylamine were developed for hybrid white OLEDs. Abstract : Two novel bipolar isomeric blue fluorophores, PPI-TPA-SO2-1 and PPI-TPA-SO2-2, consisting of electron-withdrawing phenanthro[9, 10- d ]imidazole and sulfone-locked electron-donating triphenylamine, were designed and synthesized. The sulfone lock induces a more twisted molecular conformation, and thus a higher triplet energy level and better triplet exciton confining ability compared with the analogue TPA-PPI without the sulfone lock. In addition, the introduced sulfone lock also offers the developed materials improved electron affinities and an electron dominant transporting ability. They were utilized as the blue emitter and the host for a yellow phosphorescent emitter to fabricate fluorescence–phosphorescence (F–P) hybrid white organic light-emitting diodes (WOLEDs) in a single-emissive-layer architecture, giving forward-viewing maximum current efficiencies of 44.2 and 47.6 cd A −1, power efficiencies of 49.5 and 53.4 lm W −1, and external quantum efficiencies of 14.4% and 15.6%, respectively, which are much higher than those of the devices based on TPA-PPI (29.5 cd A −1, 33.1 lm W −1, and 9.6%) due to their superior singlet and triplet exciton separation and utilization ability over TPA-PPI. These efficiencies are also the highest values ever reported for the F–P hybrid WOLEDs in a similar architecture, and their power efficiencies are even comparable with most reported highly efficient all phosphorescent WOLEDs without using any out-coupling technology.